Ghost Imaging for a Reflected Object with Large Incident Angles - Suqin Nan; Yanfeng Bai; Xiaohui Shi; Qian Shen; Hengxing Li; Lijie Qu; Xiquan Fu (IEEE Photonics Journal, 2017)
Incident angle of light source is a key factor that affects imaging resolution of direct optical imaging for a reflected target. For a large incident angle, it is easy to form the “blind area” in which the image of the object cannot be distinguished clearly. Using classical statistical optics, we study ghost imaging (GI) for a reflected object numerically and experimentally and show that by measuring the second-order correlation of light fields, a ghost-image with good quality can be retrieved in the “blind area.” Unlike transmitted ghost imaging, which is affected greatly by the transverse size of the test detector, the size has almost no effect on the resolution of reflective ghost imaging when the blind area appears.